Handbook of African American health social and behavioral interventions - Lemelle, Anthony J.; Reed, Wornie; Taylor, Sandra (Springer New York, 2011)
The U.S. Census Bureau reports particular demographic, social, and health conditions for African Americans. Population-wide, the African American community has a higher mortality rate from cancer and diabetes than the rest of the population, a higher infant mortality rate, and a lower vaccination rate for influenza and pneumonia. The contributions to this comprehensive Handbook of African American Health uncover the specific demographic conditions of the African American population, and outline social interventions for both physical and mental health at the primary, secondary, and tertiary levels. The 26 contributions to this comprehensive volume cover interventions for a diverse range of health problems, including: obesity and cardiovascular disease; diabetes; asthma and other respiratory diseases; smoking, alcohol, and recreational drug abuse; risky sexual behaviors; cancer screening, prevention, and survivorship; infant mortality; community and interpersonal violence; mental health. From a healthcare standpoint, it also examines specific interventions for treatment compliance, health care access, and community collaborations. This volume will be an invaluable resource for researchers in medical sociology, mental health studies, public health, health behavior, and African American studies.